Two New Inertial Algorithms for Solving Variational Inequalities in Reflexive Banach Spaces. (30th March 2022) - Reich, Simeon; Tuyen, Truong Minh; Sunthrayuth, Pongsakorn; Cholamjiak, Prasit
Abstract: The purpose of this paper is to introduce and analyze two inertial algorithms with self-adaptive stepsizes for solving variational inequalities in reflexive Banach spaces. Our algorithms are based on inertial hybrid and shrinking projection methods. Knowledge of the Lipschitz constant of the cost operator is not required. Under appropriate conditions, the strong convergence of the algorithms is established. We also present several numerical experiments which bring out the efficiency and the advantages of the proposed algorithms. Our work provides extensions of many known results from Hilbert spaces to reflexive Banach spaces.